Effect of Mentha aquatica L. Extract on Bloating Symptom of Irritable Bowel Syndrome Disease: A Double-Blind Randomized, Placebo-Controlled Study - Farzaneh Assadollah Pour; Assie Jokar; Mohammad Azadbakht; Ebrahim Nasiri; Zohreh Bari; Seyede Sedighe Yuosefi (Tehran University of Medical Sciences, 2021)
Irritable bowel syndrome (IBS) is a common functional gastrointestinal disorder that causes abdominal pain, distension, change of bowel habit, bloating, constipation, diarrhea, and mucus discharge along with stools. Although the disease causes long-term and agonizing pain, no ideal cure has been found for it so far. This study aimed to investigate the efficacy and compliance of Mentha aquatica L. extract for the treatment of bloating caused by IBS. This double-blind, randomized, placebo-controlled trial study was conducted in Tooba gastroenterology clinic in Sari, Iran, during 2019 (from January to May). A total of 104 patients with IBS in the age range of 20-80 years were randomly divided into two parallel groups of herbal medicine (MAC-330) and placebo. Study period consisted of a 4 weeks of administration, and 2 weeks of follow-up. IBS-associated symptoms including severity of bloating (as primary outcome) and frequency of defecation and abdominal pain were evaluated using a questionnaire before treatment, 1, 2 and 4 weeks after beginning treatment and 2 weeks after stopping treatment. There were no significant differences between the two groups in terms of their baseline characteristics (p > 0.05). The severity of bloating was significantly reduced in the both groups at fourth week (p < 0.030) and 2 weeks after stopping intervention (sixth week) (p < 0.026). The frequency of defecation has increased with the onset of the intervention until the fourth week of the treatment which was not significant. The abdominal pain reduced during the 4 weeks' intervention, but it was not significant. Based on the obtained results, MAC-330 could not be used as an effective treatment for patients with IBS in short time; however, it reduces the abdominal bloating and pain in these patients, especially in the long-term use.